(untitled) (Research, Society and Development, 2022)
Children are vulnerable when they are choking, as they have less experience and ability to ask for help, and it is important that adults know how to perform the Heimlich maneuver, clearing the airways. The objective of this research is to understand how the Heimlich maneuver works as a pediatric first aid technique. This research is an integrative literature review, carried out during the months of August and October 2022, the data used were extracted from the databases: VHL, SCIELO, LILACS and MEDLINE. The descriptors were: “Heimlich Maneuver”, “First Aid”, “Child Health” and “Respiratory Tract Obstruction”. The inclusion criteria were studies in Portuguese, free of charge and within the time frame from 2016 to 2022. The exclusion criteria were duplicate articles, abstracts, reviews and theses. After selecting the studies, according to the inclusion and exclusion criteria, only 6 articles were selected to compose the final sample. It was concluded that the Heimlich maneuver must be performed by positioning oneself behind the victim, with arms around the waist and closed hands positioned below the xiphoid process, making strong and rapid movements from the bottom up, in order to create a artificial cough, which can expel the object or material that resulted in choking, such a first aid maneuver is responsible for saving countless lives.